Angry listening and a listening God: Liturgical-theological reflections - Wepener, Cas; Van der Merwe, Suzanne (Stellenbosch Theological Journal, 2022)
The potential value of the bodily expression of anger and lament has been explored in literature, also the value and need for rituals and liturgies of anger and lament. One aspect of angry liturgy that has not yet received much attention is the spiritual practice of listening to anger and lament. This article explores listening to anger in the liturgy as a faith practice. It is argued that embodied liturgical expressions of anger should more readily be accompanied by angry listening. The theological premise of the argument is the God of the Christian liturgy is not only the God who speaks but, also and importantly, the God who listens, and that this listening (to anger) extends to both God and those encountering God in liturgy in a theonomic reciprocal way.